Kelompok Kerja Guru dan Perannya dalam Meningkatkan Mutu Pembelajaran PAI di Sekolah Dasar - Asalihin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2021)
The quality of Islamic Education learning is still faced with various problems, even though the elements that should exist have carried out their respective functions, therefore this research aims to describe the role of the teacher working group in improving the quality of PAI learning. To achieve the intended objectives, this research was designed with a qualitative approach, the data source of this research consists of the chairman and members of the Pai Teacher Working Group (KKG), principals and some learners, research data obtained through focus group discussions, observations, interviews and documentation studies. All data are analyzed interactively according to the stages of collection, reduction, presentation, and verification. From the results of the research that has been done and from the objectives contained in the research can be concluded that the role of the Islamic Religious Education KKG in order to improve the quality of learning PAI Elementary School is KKG-PAI as a forum for religious teachers by conducting various programs of coaching activities through regular monthly meetings, helping religious teachers in order to solve all problems encountered by teachers in the classroom in carrying out their duties and basic functions as PAI teachers.